DIRECTING FUNCTION OF NURSE MANAGER AND ASSOCIATE NURSE'SCOMPLIANCE IN PRACTICING HAND HYGIENE - Achmad Syaifudin; Mona Saparwati (Jurnal SMART Keperawatan, 2024)
Hand hygiene is a general term that applies to wash hands with antiseptic and handrub antiseptic. The implementation of operationalstandards of handwashing compliance procedures requires directing function from the Nurse Manager. The purpose of this studywas to determine the relationship between directing function of Nurse manager and associate nurse compliance in performing ha ndhygiene. The method used in this study was descriptive correlation with cross sectional approach. The population was allimplementing nurses at Inpatient Room of Ungaran General Hospital as many as 82 nurses. All samples were taken by totalsampling. The collecting data tool used a questionnaire of nurse’s perception on directing function of nurse manager and observationsheet on hand hygiene. The research results showed that most of nurse manager performed good directing function as many as 76people (92.7%), most of the nurses were compliance in practicing patient safety: five moment hand hygiene as many as 78 people(95,1%). The result of statistical test using Fisher's Exact Test obtained p value of 0,001 (α = 0,05). There is a correlatio n betweennurse’s perception on directing function of nurse manager with associate nurse compliance in practicing hand hygiene in inpatientroom of Ungaran General Hospital. Nurses need to increase patient safety awareness and compliance hand hygiene to minimize th eincidence of nosocomial infections.